DETERMINING THE OPTIMAL WATER MIST PARTICLE SIZE RANGE FOR EFFECTIVE FIRE SUPPRESSION IN COLD STORAGE FACILITIES - LEVCHENKO, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Within this study, to examine the possibilities of applying water mist technology, a specialized experimental platform was developed and assembled. This analysis allowed for the determination of key parameters such as the initial decomposition temperature, the rate of release of combustible gases, and other important indicators that define the material's behavior under thermal stress. During the experiments, various fire parameters were carefully measured and analyzed, including flame temperature, fire spread rate, smoke level, combustion product concentration, and other key characteristics of the fire scene. Firstly, the study revealed that fires in cold storage facilities are characterized by re-ignition, which is independent of the insulation material's location. Even at a nozzle pressure of 1 MPa, re-ignition was still observed. However, when the nozzle pressure was increased to 3 MPa and 9 MPa, re-ignition did not occur. Secondly, during water mist fire suppression, an effective reduction in the concentration of CO produced during the fire was observed. The effect of reducing CO concentration is particularly noticeable at a nozzle pressure of 9 MPa. Simultaneously, the water mist system also contributes to reducing the concentration of O2, creating a suffocating environment for the flame and helping to control the fire. The study also confirmed that as pressure increases, the size of the water mist droplets decreases. During the fire suppression process, the smaller the water particle diameter, the greater the proportion of droplets that evaporate, and the greater the increase in volume. Within this study, a water particle size range of 100-200 μm was investigated, and a particle size range that provides the best fire suppression effect in cold storage facilities was identified – 110-140 μm. This specific particle size range of fine water mist is the most suitable for fire protection in cold storage facilities.
Keywords: water mist; water mist temperature; pressure; cold storage fires; fire extinguishing